THE CORONAVIRUS PANDEMIC AND ISSUES OF SOCIAL RESPONSIBILITY SUMMARY (International Journal of Innovative Technologies in Economy, 2024)
Topicality. The coronavirus pandemic has led to an even greater increase in corporate social responsibility activities. Thus, the sense of social responsibility towards the society, the medical field and the areas most affected by the pandemic has developed a culture of corporate social responsibility in many organizations. The projects implemented in this framework have helped to reduce the effects of the pandemic and reminded once again the importance of social responsibility for both companies and society.Aim and tasks. Your article's main purpose is to analyze the social responsibilities of companies in the face of social problems caused by the coronavirus pandemic. Based on the examples taken at this time, negative and positive aspects and missing aspects should be revealed.Research results. Social responsibility, which is developing during the Covid-19 pandemic, shows that companies are now giving importance to moral advantages as well. The impact on business, economic and social aspects, as well as the image created by corporate social responsibility projects and the support received by society due to the impact of the coronavirus pandemic are part of sustainable development.Conclusion. The development in this field in recent years shows that the conducted researches are carried out, the results obtained and the proposals made are already implemented and have started to show their results. The researches proved that during the pandemic, many companies have signed useful projects with a deeper understanding of their social responsibility. The pandemic factor was also taken into account as an unexpected force majeure in our research conducted with the need for further development of this field in modern times.